Relation of Periodontitis and Metabolic Syndrome With Gestational Glucose Metabolism Disorder. Issue 2 (1st February 2014) - Bullon, Pedro; Jaramillo, Reyes; Santos‐Garcia, Rocio; Rios‐Santos, Vicente; Ramirez, Maria; Fernandez‐Palacin, Ana; Fernandez‐Riejos, Patricia
Abstract : Background: Gestational diabetes mellitus (GDM) and metabolic syndrome have been related to periodontitis. This study's objective is to establish the relationship between them in pregnant women affected by gestational glucose metabolism disorder. Methods: In 188 pregnant women with positive O'Sullivan test (POT) results, an oral glucose tolerance test (OGTT) was performed to diagnose GDM. The mother's periodontal parameters, age, prepregnancy weight and height and body mass index (BMI), blood pressure, gestational age, and birth weight were recorded at 24 to 28 weeks of pregnancy, as well as levels of glucose, C‐reactive protein, triglycerides, glycated hemoglobin (HbA1c), and total, low‐density lipoprotein, high‐density lipoprotein (HDL), and very‐low‐density lipoprotein (VLDL) cholesterol levels. Results: Prepregnancy weight, prepregnancy BMI, systolic and diastolic blood pressure, VLDL cholesterol, and glucose parameters were higher in GDM compared with POT ( P <0.05). VLDL cholesterol, triglycerides, and 2‐hour OGTT were higher in patients with periodontitis than in patients without periodontitis ( P <0.05). HbA1c, triglycerides, and 1‐ and 2‐hour OGTT were positively related with probing depth and clinical attachment level; blood glucose was related only to bleeding on probing ( P <0.05). HbA1c, basal OGTT, and 1‐ and 2‐hour OGTT were positively related to prepregnancy BMI and blood pressure; HDL cholesterol was negatively related to prepregnancy BMI; C‐reactive protein was positively related to prepregnancy BMI and diastolic blood pressure ( P <0.05). Conclusion: These data support the relationships among periodontal disease and some biochemical parameters such as lipid and glucose data in pregnancy, and also among metabolic syndrome and biochemical parameters.